PENGEMBANGAN BAHAN AJAR SENI RUPA BERMEDIA POWERPOINT KELAS X SMK - Irwan, Irwan; Sjarkawi, Sjarkawi; Murbojono, Rahmat (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
Fine art learnin.g in vocational high school (SMK) 2 Batanghari has some problems, such as 1) the lack of fine art teaching materials as source of school, 2) the teachers of fine art do not use media yet, like power point in conveying massage of learning process to students, 3) teaching materials are used in learning process is less attractive, 4) the culture Jambi areas not exist in previous teaching materials before. The research of fine art power point medias development adopted of design model instructional competence approach system (DSI-PK), which consists of 3 steps, namely; 1) needs analysis, 2) development, and 3) evaluation.The purpose of fine art development of power point media are: 1) producing, how to develop teaching materials of fine art power point media X class SMK, 2) develop teaching materials of fine art power point media in accordance with requirements of development, 3) producing of fine art teaching materials power point media engaging and effective for students of class X vocational learning, 4) producing how to use teaching materials of fine art power point media, 5) developing of fine art teaching materials power point media for teachers and class X SMK students. Teaching materials of fine art vocation some expert like material expert, media expert, design expert. The three member of them giving evaluation of teaching materials with good/interest/appropriate. Peers consist of teacher have education of fine art background give it excellent/very interesting/very suitable for teaching materials with percentage value of 81,77%. The interesting of teaching materials can be seen from response and feedback provided by teachers and students to the teaching materials. The anthusiasm of the students is very good for teaching materials provided during product trials. The responseof teachers to the teaching materials is very good, because teaching materials made with attractive colour, harmonious and letters of variation. The effectivness of teaching materials seen of improving student learning outcomes seen with minimal completeness criteria obtained through the result of free test and post test. It is recommended that teachers in delivering learing materials to the students using relevant learning resources for the next teaching learning developer, to develop teaching materials accordance with requirement of development research learning more wxciting by using media than just lecturing in delivering teaching materials to the student should be use the media in order learning activities are varied and not monotonous. Keyword: interactive cd, powerpoint, konvensional, cognitive style and learning outcomes